Constant sectional curvature surfaces with a semi-symmetric non-metric connection - Aydin, Muhittin Evren; Lopez, Rafael; Mihai, Adela (Academic Press Inc Elsevier Science, 2025)
Consider the Euclidean space R-3 endowed with a canonical semi-symmetric non-metric connection determined by a vector field C is an element of X(R-3). We study surfaces when the sectional curvature with respect to this connection is constant. In case that the surface is cylindrical, we obtain full classification when the rulings are orthogonal or parallel to C. If the surface is rotational, we prove that the rotation axis is parallel to C and we classify all conical rotational surfaces with constant sectional curvature. Finally, for the particular case 12 of the sectional curvature, the existence of rotational surfaces orthogonally intersecting the rotation axis is also obtained. (c) 2024 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Rotational surface; Sectional curvature; Semi-symmetric connection; Non-metric connection